2018
DOI: 10.1155/2018/4051232
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry and Blueberry Anthocyanin Supplementation Counteract High‐Fat‐Diet‐Induced Obesity by Alleviating Oxidative Stress and Inflammation and Accelerating Energy Expenditure

Abstract: Many studies indicate that an anthocyanin-rich diet has beneficial effects preventing metabolic disease. In the present study, the molecular mechanism underlying the antiobesity effect of consuming blackberry anthocyanins (BLA) and blueberry anthocyanins (BBA) was investigated in high-fat-diet- (HFD-) fed C57BL/6 mice. Sixty mice were administered a low-fat diet (LFD), a HFD, or a HFD plus orlistat, and BLA or BBA in their daily food for 12 weeks. As a result, the consumption of BLA and BBA inhibited body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 52 publications
4
57
1
1
Order By: Relevance
“…In contrast to ndings made in human interventions, numerous animal studies reported bene ts of blueberries alone or mixed with other berries on weight management (42)(43)(44), markers of glucose/insulin resistance or sensitivity (10,(42)(43)(44)(45)(46), lipid pro le (42,47,48), vascular health (49,50), kidney function (51) or in ammatory markers (10,(42)(43)(44)(50)(51)(52)(53). Results from studies assessing other MetS phenotype parameters have been consistent with our ndings overall.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to ndings made in human interventions, numerous animal studies reported bene ts of blueberries alone or mixed with other berries on weight management (42)(43)(44), markers of glucose/insulin resistance or sensitivity (10,(42)(43)(44)(45)(46), lipid pro le (42,47,48), vascular health (49,50), kidney function (51) or in ammatory markers (10,(42)(43)(44)(50)(51)(52)(53). Results from studies assessing other MetS phenotype parameters have been consistent with our ndings overall.…”
Section: Discussionsupporting
confidence: 87%
“…Anti-oxidant therapies exert beneficial effects on many diseases characterized by inflammation consequent to impaired redox homeostasis [88][89][90]. In the context of inflammatory diseases, systemic oxidative stress is detected as decreased total free thiol levels (free sulfhydryl groups of cysteine in proteins such as albumin as well as low-molecular-weight free thiols, for example cysteine, glutathione, homocysteine and related species).…”
Section: Treatment With Gsh and Thiolsmentioning
confidence: 99%
“…Functional ingredients of blueberry restrain the growth and metastasis of breast cancer cells by modulating the PI3K/AKT/NF-κB pathway [ 113 ]; the expression of caspase-9 and cytochrome c as well as the downregulation of the methylation of p53 of blueberry anthocyanins suppressed the proliferation and induced G2/M cell arrest and oral cancer cells apoptosis [ 114 ]. Blackberry anthocyanins and blueberry anthocyanins can ameliorate diet-induced obesity by alleviating oxidative stress and inflammation and quickening energy expenditure [ 115 ]. Blueberry peel extracts reduced weight and fat accumulation in obese rats by the downregulation of three genes and the reduction of phospho-Akt adipogenic factor in obese cells [ 116 ].…”
Section: Major Mechanisms and Structural Activity Of Blueberry Commentioning
confidence: 99%